Analysis Of Product Quality And Promotion On Purchasing Decisions For Nias Specialty Foods At Wery Bakery - Eldaa Yuannda Harefa; Yossie Rossanty (Journal of Management, Economic, and Accounting, 2026)
This study aims to determine the effect of product quality and promotion on the decision to purchase Nias souvenirs at Wery Bakery. This study was conducted from December 2024 to April 2025. The population and sample of this study consisted of 86 respondents. Data processing was performed using SPSS Version 26. Data testing was conducted using classical assumption tests and multiple linear regression. The calculated t-value for product quality was 3.565 > t-table 1.66 and significance 0.001 < 0.05, indicating that product quality partially has a positive and significant effect on purchasing decisions. The t-value for promotion was 15.667 > t-table 1.66 and significance 0.000 < 0.05, so promotion partially had a positive and significant effect on purchasing decisions. The F test results show that the calculated F value is 561.965 > the table F value of 2.48 with a significance value of 0.000 < 0.005, meaning that product quality and promotion simultaneously have a significant effect on purchasing decisions. The R² test result is 0.931, meaning that 93.1% of purchasing decisions can be obtained and explained by the variables of product quality and promotion.